OP0280 Recurrent Pericarditis in Children and Adolescents: A Large, Multicentric Case-Series and Implications for the Pediatric Rheumatologist. (10th June 2014) - Di Blasi Lo Cuccio, C.; Gattorno, M.; Cantarini, L.; Cimaz, R.; Gaspari, S.; Marcora, S.; Insalaco, A.; Imazio, M.; Breda, L.; Martini, A.; Brucato, A.
Abstract : Background: Acute pericarditis is defined as at least 2 of the following: typical chest pain (sharp and pleuritic, improved by sitting up and leaning forward), pericardial friction rub, suggestive EKG changes (widespread ST elevation or PR depression), new or worsening pericardial effusion. Pericarditis may recur in 15-30% of cases; these children are frequently followed by pediatric Rheumatologists. At present the largest case series described 15 children affected by recurrent pericarditis. Objectives: This is a multicenter, retrospective cohort study including all consecutive cases of recurrent pericarditis with at least 2 recurrences in pediatric patients seen in 7 referral centers in Italy. Methods: We analyzed 107 children; the mean age at the time of the first attack was 11, 1 years; 67 were males and 40 females. Results: The mean recurrence number was 4.8 (2-25); pericarditis was idiopathic in the majority of cases (88%), post-pericardiotomic in 10%, related to Familiar Mediterranean fever in 2%. Most children had fever and CRP elevation at disease onset (77% fever, 93% CRP elevation), and so was pericardial effusion (76%: typically mild, with cardiac tamponade in 13%, only at disease onset), while pericardial rub and EKG changes were detected in a smaller number of patients (28% and 45% respectively). After a mean follow-up of 73 months, none of the patients with idiopathic RP developed a systemic autoimmune disease (even if ANA was positive in 19%) or was found as having an infectious disease. 80% children were treated with NSAIDs, 64% with steroids and 63% with colchicine. Refractory cases were treated with immunosuppressant drugs (AZA: 4, MTX: 2, IVIG: 1, Antimalarials: 5, CSA: 1), and 11 with Anakinra. Children treated with corticosteroids experienced more recurrences (5, 9 vs 2, 6, p<0, 05) and more disease-related hospitalization (83, 4% vs 39, 5%, p<0.05). Colchicine halved the attacks number: N. attacks per patient per year before colchicine: 3, 8; after colchicine: 1.6 (p<0.05). Anakinra was effective, with less side effects than corticosteroids, but disease recurred when it was discontinued. Long term outcome was good, with no evolution in constrictive pericarditis, cardiomyopathy or systemic rheumatic diseases. Conclusions: This is the largest ever published case-series on pediatric recurrent pericarditis. Because of lack of standardized treatment guidelines, we believe that our data will help clinicians in manage these children, typically treated with rheumatological drugs. Corticosteroids should be used with extreme caution and NSAIDs remain the mainstay of the therapy. Anti-IL1 may be useful in very selected cases. The long term outcome is good. References: Imazio M, et al. A randomized trial of colchicines for acute pericarditis. New Engl J Med 2013; 369:1522-8. Gaspari S. et al. New insights in the pathogenesis and therapy of idiopathic recurrent pericarditis in children. Clin Exp Rheumatol 2013;31:788-94. Raatikka M et al. Recurrent pericarditis in children and adolescents. Report of 15 cases. J Am Coll Cardiol 2003;42:759-64. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.1952